2014
DOI: 10.1002/cb.1487
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment events in shopping malls—profiling passive and active participation behaviors

Abstract: This paper presents an empirical framework for operationalizing passive versus active participation in the context of shopping mall entertainment events (e.g., school holiday events and fashion shows) and assesses the framework's utility for segmenting and profiling shopping mall entertainment audiences. Exploratory factor analysis of data collected at shopping mall events revealed two distinct dimensions, “relax and be entertained” and “socialize and explore,” reflecting passive and active participation, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Although the term “mall experience” is rarely found in the literature, a large body of studies has examined the experiences of customers in shopping malls. The term experience in the context of shopping malls has been related to hedonic shopping motivations (Arnold and Reynolds, ), emotional reactions (Machleit and Eroglu, ), perceived attributes (Ganesh et al ., ), activities (Bloch et al ., ; Sit and Birch, ), excitement (Baker and Wakefield, ), and atmosphere (Dennis et al ., ). This diverse literature suggests that the mall experience is a multidimensional or higher‐order construct derived from the interaction between customers' cognitive, emotional, behavioral, and social reactions and the mall environment (Haytko and Baker, ).…”
Section: Customers' Experiences In Shopping Mallsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the term “mall experience” is rarely found in the literature, a large body of studies has examined the experiences of customers in shopping malls. The term experience in the context of shopping malls has been related to hedonic shopping motivations (Arnold and Reynolds, ), emotional reactions (Machleit and Eroglu, ), perceived attributes (Ganesh et al ., ), activities (Bloch et al ., ; Sit and Birch, ), excitement (Baker and Wakefield, ), and atmosphere (Dennis et al ., ). This diverse literature suggests that the mall experience is a multidimensional or higher‐order construct derived from the interaction between customers' cognitive, emotional, behavioral, and social reactions and the mall environment (Haytko and Baker, ).…”
Section: Customers' Experiences In Shopping Mallsmentioning
confidence: 99%
“…Some studies of mall customers' activities take into account the active role of customers as co‐creators of their own experience. These studies suggest that mall activities can be divided into four categories: consumption activities , such as making planned and unplanned purchases and browsing display windows; social activities , such as unplanned meetings with acquaintances and watching others; participation in activities initiated by the mall management ; and entertainment activities , such as going to see a movie or sitting in eateries (Bloch et al ., ; Ruiz et al ., ; Gilboa, ; Sit and Birch, ). These studies show that customers' routine practices make them co‐creators of their own experience (Carù and Cova, ).…”
Section: Customers' Experiences In Shopping Mallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional services and entertainment. Studies have indicated that shopping centers have improved their own image and attractiveness due to the inclusion of other services such as food, relaxation, and entertainment services (Bellenger et al, 1977;Haynes and Talpade, 1996;De Nisco and Rosaria Napolitano, 2006;El-Adly, 2007;Ahmad, 2012;Sit and Birch, 2014). This can be considered to be a favorable offer for leisure, constituted by diverse factors influencing attendance motivations (Sit et al, 2003).…”
Section: Identification Of Attraction Factors and Establishment Of Thmentioning
confidence: 99%
“…The information given about a product by food companies is important for consumer protection, decision-making processes, and competition. Labels which are the most common form of this transfer of knowledge facilitate consumers to make healthy and informed choices by means of information about the ingredients, price, expiration date, origin and nutritional value of the product (Yılmaz et al, 2009;Uçar et al, 2012;Sit and Birch, 2014).…”
Section: Introductionmentioning
confidence: 99%